Implementasi Integrasi Keilmuan dalam Tradisi Kajian Hadis pada Prodi Ilmu Hadis Uin Alauddin Makassar - Nofri Andy.N,; Ridha, Muhammad (Tahdis: Jurnal Kajian Ilmu Al-Hadis, 2024)
The lack of interest in the Hadith Science study program is caused by public perception about the heavy curriculum load and difficult job prospects. Hadith Science UIN Alauddin Makassar comes with a discourse on scientific integration that has its own appeal for Islamic science enthusiasts in the Eastern Indonesia region. This study reveals the implementation of scientific integration in the Hadith Science study program at UIN Alauddin Makassar. The results of the study show that student input from Madrasahs and Islamic boarding schools in South Sulawesi and throughout Eastern Indonesia strengthens the quality so that it can be useful in society and provides special attention to students from public schools by implementing an Islamic science strengthening program